UNRAVELING INSTABILITY: THE POLITICS BEHIND COUPS IN FRANCOPHONE AFRICA - Santos , João Carlos Pereira dos; Almeida, Ana Luiza Oliveira (Ayden International Journal of Law, Political Science, and Administration, 2025)
In recent years, Francophone Africa has experienced a surge in political unrest characterized by a series of coups d'état, disrupting the democratic progress achieved since the 1990s. This article delves into the underlying causes, implications, and international responses to these coups, particularly focusing on notable occurrences in Mali, Burkina Faso, and Niger. By employing a multidimensional analysis, encompassing political, economic, and social dynamics, the article aims to unravel the intricate factors that precipitated these coups. Understanding these complexities is imperative for devising effective strategies to address and mitigate the recurrence of such destabilizing events. Through a comprehensive examination of the region's socio-political landscape, this study endeavors to provide insights into the root causes of political upheaval, offering avenues for fostering stability and democratic resilience.